Efektifitas Kompres Hangat dan Nafas dalam terhadap Nyeri Perut Pasien Typus Abdominalis di RSUD Dr. R Goeteng Taroenadibrata Purbalingga - Taat Sumedi (JURNAL KEPERAWATAN MERSI, 2019)
Abdominalis Typhus is a disease that attacks the gastrointestinal tract in the small intestine. This disease is occupying sequence of number one for three consecutive in RSUD dr. R. Goeteng Taroenadibrata Purbalingga. This objective of this research is to determine the effectivity of warm compresses and deep breath towards patient’s abdominal pain of abdominalis typhus in RSUD dr. R. Goeteng Taroenadibrata Purbalingga. Type of study is a quasi experimental design with pretest posttest with control group design. Sampling using the purposive sampling techniques. Sample as many as 76 respondent, that 38 responden were given a warm compresses treatment and 38 other respondents as control group were given a deep breath. Data analysis is done by using univariate analysis and independent t-test. The result of this research there is a significant decrease in pain level after warm compresses amounted to 2.053. While those given a deep breath has decrease amounted to 0.921. Independent t test results indicate a warm  compresses are more effective in decreasing the level of pain in patient’s abdominalis typhus compared with a deep breath in the p value 0,001.